1998
DOI: 10.1038/sj.bmt.1701139
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal fluctuations in cytomegalovirus load in bone marrow transplant patients: relationship between peak virus load, donor/recipient serostatus, acute GVHD and CMV disease

Abstract: Summary:Quantitative competitive PCR was used to monitor the quantity of cytomegalovirus (HCMV) in 1647 blood samples from 110 BMT recipients. DNAemia was detected in 49/110 (45%) of the patients, of whom 15/49 experienced HCMV disease. Peak virus load during surveillance was elevated in symptomatic (median 4.5 log 10 genomes/ml) vs asymptomatic patients (median 3.6 log 10 genomes/ml, P = 0.002) and was also significantly elevated in HCMV seropositive recipients of seronegative marrow, (R+D−, median 5.0 log 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
121
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(126 citation statements)
references
References 38 publications
4
121
1
Order By: Relevance
“…[20][21][22] Numerous publications have shown the use of a variety of molecular amplification methods. [23][24][25][26][27][28] In our previous report, we retrospectively demonstrated that quantitative real-time PCR was more sensitive and correlated with the effects of antiviral treatment better than CMV antigenemia in a small number of patients with CMV gastroenteritis. 13 In this prospective study with more patients, we confirmed our previous observation and that real-time PCR-guided preemptive therapy more effectively but not completely prevented the occurrence of CMV diseases.…”
Section: Discussionmentioning
confidence: 99%
“…[20][21][22] Numerous publications have shown the use of a variety of molecular amplification methods. [23][24][25][26][27][28] In our previous report, we retrospectively demonstrated that quantitative real-time PCR was more sensitive and correlated with the effects of antiviral treatment better than CMV antigenemia in a small number of patients with CMV gastroenteritis. 13 In this prospective study with more patients, we confirmed our previous observation and that real-time PCR-guided preemptive therapy more effectively but not completely prevented the occurrence of CMV diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Similar conclusions have been drawn from recent studies involving other immunosuppressed cohorts. 38,[42][43][44][45][46][47][48][49][50] Quantitative PCR for CMV appears to be an effective diagnostic tool in identifying patients with disease. In addition, PCR detection of DNA targets is less sensitive to sample handling than other diagnostic tests.…”
Section: Predictive Value Of Quantitative Pcrmentioning
confidence: 99%
“…The patients compromised renal transplant (nZ12) (Hassan Walker et al 1999), liver transplant (nZ18) (Cope et al 1997) and bone marrow transplant (nZ13) (Gor et al 1998) recipients and 16 HIV-infected individuals (Bowen et al 1997). HCMV diseases conformed to the International Workshop definition (Ljungman et al 2002) and included HCMV retinitis (nZ17), gastrointestinal disease (nZ7), hepatitis (nZ4), pyrexial debilitating disease (nZ14) and HCMV pneumonitis (nZ14).…”
Section: Methodsmentioning
confidence: 99%
“…These studies have shown that viral load is a dominant risk factor for HCMV disease (Cope et al 1997;Gor et al 1998;Spector et al 1998;Emery et al 1999a,b;Hassan-Walker et al 1999;Limaye et al 2001). In addition, kinetics of replication during the early phases of active replication have been defined and used to estimate the basic reproductive number of HCMV (Emery et al 2002) and to provide prognostic information in the immunocompromised host (Emery et al 2000;Schafer et al 2001).…”
Section: Introductionmentioning
confidence: 99%